2007
DOI: 10.1523/jneurosci.4341-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Subthreshold Calcium Current and Sodium Current in Spontaneous Firing of Mouse Midbrain Dopamine Neurons

Abstract: We used a preparation of acutely dissociated neurons to quantify the ionic currents driving the spontaneous firing of substantia nigra pars compacta neurons, isolated from transgenic mice in which the tyrosine hydroxylase promoter drives expression of human placental alkaline phosphatase (PLAP) on the outer surface of the cell membrane. Dissociated neurons identified by fluorescent antibodies to PLAP showed firing properties similar to those of dopaminergic neurons in brain slice, including rhythmic spontaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
317
9
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 287 publications
(361 citation statements)
references
References 68 publications
33
317
9
2
Order By: Relevance
“…The subthreshold Ca 2+ -K + oscillatory mechanism underlies the generation of low frequency background firing in a significant subpopulation of DA neurons [7][8][9][10][11][12][13][14][15][16][17][18]51]. However, a number of studies suggest a contribution of Ca 2+ -independent currents to oscillations [26,19,25,27,46]. In accord with these studies, we found that, if considered in isolation, the Ca 2+ -K + oscillatory mechanism provides type II excitability, which is incompatible with the experiments reproduced above.…”
Section: Influence Of Intrinsic Currents On the Type Of Excitabilitysupporting
confidence: 73%
See 3 more Smart Citations
“…The subthreshold Ca 2+ -K + oscillatory mechanism underlies the generation of low frequency background firing in a significant subpopulation of DA neurons [7][8][9][10][11][12][13][14][15][16][17][18]51]. However, a number of studies suggest a contribution of Ca 2+ -independent currents to oscillations [26,19,25,27,46]. In accord with these studies, we found that, if considered in isolation, the Ca 2+ -K + oscillatory mechanism provides type II excitability, which is incompatible with the experiments reproduced above.…”
Section: Influence Of Intrinsic Currents On the Type Of Excitabilitysupporting
confidence: 73%
“…Persistent sodium current is known to amplify subthreshold oscillations [69] and increases neural excitability of DA neurons by contributing to spontaneous depolarization in between the spikes [25]. Consistent with experimental observations, the subthreshold sodium current population receiving the tonic synaptic inputs.…”
Section: The Role Of the Subthreshold Sodium Currentsupporting
confidence: 69%
See 2 more Smart Citations
“…Neuroprotective effects of isradipine are achieved at the plasma concentration that is obtained within the safe dose range for human administration10, 11 and consistent with the tolerable dosage identified in our phase II study of isradipine in PD (STEADY‐PDII) 12. Isradipine is the most potent of the clinically available Cav1.3 DHPs and has excellent central nervous system penetration suggesting it is the optimal DHP to target this novel mechanism of neuroprotection 13, 14…”
Section: Introductionsupporting
confidence: 68%